Enhancement of fructosyltransferase and fructooligosaccharides production by A. oryzae DIA-MF in Solid-State Fermentation using aguamiel as culture medium - Muñiz-Márquez, Diana B. (2016)
The aim of this work was to improve the production of fructosyltransferase (FTase) by Solid-State Fermentation (SSF) using aguamiel (agave sap) as culture medium and Aspergillus oryzae DIA-MF as producer strain. SSF was carried out evaluating the following parameters: inoculum rate, incubation temperature, initial pH and packing density to determine the most significant factors through Box-Hunter and Hunter design. The significant factors were then further optimized using a Box-Behnken design and response surface methodology. The maximum FTase activity (1347 U/L) was obtained at 32 °C, using packing density of 0.7 g/cm3. Inoculum rate and initial pH had no significant influence on the response. FOS synthesis applying the enzyme produced by A. oryzae DIA-MF was also studied using aguamiel as substrate.